PENGARUH KOMUNIKASI ORGANISASI DAN KEPUASAN KERJA TERHADAP KOMITMEN ORGANISASI GURU SD SANTO FRANSISKUS DI LAMPUNG - Magdalena Suliyem (Universitas Negeri Jakarta, 2016)
This study aims to determine the effect of (1) organizational communication, (2) job satisfaction, (3) organizational commitment of primary school sint. Francis ln Lampung. This research uses a survey method with a quantitative-causal approach using path analyses. 88 responders were involved by sending their feedback within the questioner. Those responders were decided using simple random sampling among all teachers that working at the predetermined location. The results showed that: first, there are positif influence between the organizational communication and organizational commitment of teachers in schools. Secondly, there is positif influence between job satisfation and organizational commitment of teachers in schools. Third, there is positif influence between organizational communication and job satisfaction of teachers in schools.